The Impact of Covid-19 on The Incidence of Periodontitis Cases and its Therapeutic Management During The Pandemic - Ni Putu Idaryati (Jurnal Kesehatan Gigi, 2023)
ABSTRACTIntroduction: Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2. Periodontitis is an infection of the periodontal tissue that causes inflammation with the potential for the spread of intravascular microorganisms throughout the body. According to Riskesdas, periodontitis cases in Indonesia reached 74.1%. The purpose of this study was to determine the impact of COVID-19 on the incidence of periodontitis cases and their therapeutic management during the pandemic. Methods: Descriptive qualitative research using primary and secondary data in three primary health care on Kediri Tabanan. Results: The incidence of Periodontitis is in the first rank with the most cases in two Puskesmas. Oral drug therapy and extraction are the treatment options used in the treatment of periodontitis cases during the pandemic. Discussion: The high incidence of periodontitis during the COVID-19 pandemic is caused by patients who are afraid to visit the dentist. Patients coming to the dentist when the condition of the teeth is damaged and experiencing mobility. In addition, the dental polyclinic only serves patients with medical emergencies. Tools in the dental polyclinic are damaged due to never being used during the pandemic. Transmission process that occurs through aerosols produced in the practice of dental services makes the therapy be limited. Drug administration and extraction are options in the management of periodontitis cases. Conclusion: The impact of the COVID-19 pandemic has resulted in a high number of periodontitis cases. Oral medication administration and extraction an option for periodontitis therapy in the dental polyclinic of primary health care.